2022
DOI: 10.1038/s41467-022-35310-5
|View full text |Cite
|
Sign up to set email alerts
|

Upper gut heat shock proteins HSP70 and GRP78 promote insulin resistance, hyperglycemia, and non-alcoholic steatohepatitis

Abstract: A high-fat diet increases the risk of insulin resistance, type-2 diabetes, and non-alcoholic steato-hepatitis. Here we identified two heat-shock proteins, Heat-Shock-Protein70 and Glucose-Regulated Protein78, which are increased in the jejunum of rats on a high-fat diet. We demonstrated a causal link between these proteins and hepatic and whole-body insulin-resistance, as well as the metabolic response to bariatric/metabolic surgery. Long-term continuous infusion of Heat-Shock-Protein70 and Glucose-Regulated P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 104 publications
0
14
0
Order By: Relevance
“…Notably, we observed a signi cant upregulation of GRP78 expression in fatty hepatocytes, leading us to speculate that GRP78 also promoted lipid accumulation in hepatocytes. Studies have demonstrated that upregulation of GRP78 contributed to insulin resistance and non-alcoholic steatohepatitis (NASH) in mice (Angelini et al, 2022), and activated the IRE1α/XBP1s signaling pathway, promoting lipid accumulation in the hepatopancreas of megalobrama amblycephala (Cao et al, 2019). Furthermore, inhibition of GRP78 has been shown to increase lipid toxicity and reactive oxygen species (ROS) generation in latency competent cancer (LCC) cells (Cook et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, we observed a signi cant upregulation of GRP78 expression in fatty hepatocytes, leading us to speculate that GRP78 also promoted lipid accumulation in hepatocytes. Studies have demonstrated that upregulation of GRP78 contributed to insulin resistance and non-alcoholic steatohepatitis (NASH) in mice (Angelini et al, 2022), and activated the IRE1α/XBP1s signaling pathway, promoting lipid accumulation in the hepatopancreas of megalobrama amblycephala (Cao et al, 2019). Furthermore, inhibition of GRP78 has been shown to increase lipid toxicity and reactive oxygen species (ROS) generation in latency competent cancer (LCC) cells (Cook et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rodent models of obesity display increased levels of GRP78 in the jejunal secretome, indicating that intestinal epithelial cells may be the primary source of GRP78 secretion in response to lipid overload. 14 …”
Section: Grp78 Roles Beyond the Ermentioning
confidence: 99%
“…It is now widely accepted that, following cellular stress, HSPs can be released into the extracellular compartment from a variety of cells, including intestinal epithelial cells, 14 and act as a proinflammatory signal. 15 , 11 …”
Section: Introductionmentioning
confidence: 99%
“…Both CD147 and GRP78 are tumour markers [75] , [76] , indicating why cancer patients have a higher risk of severe COVID-19 [77] . Furthermore, it was recently shown that the expression of GRP78 is increased in the jejunum of rats fed a high fat diet [78] .…”
Section: Other Receptors and Factors Involved In Sars-cov-2 Infectionmentioning
confidence: 99%